Attribute-based Credentials for Trust Identity in the Information Society - Rannenberg, Kai (Springer, 2015)
When the preparations for the ABC4Trust proposal started in 2009, it could not be foreseen how much the world would change until today. However, the need for in formation privacy and security continued to grow and got increasingly recognized thereby making the results of ABC4Trust more relevant than ever.Also, we see con firmed one firm belief the project set out with: for privacy-friendly solutions to get accepted to a much larger degree, they need to be explained and trialled thoroughly and with a solid technical background. Editing and writing this book would not have been possible without the many helping hands that dedicated their knowledge, expertise, and time to make this endeavour a success...